Identifying and understanding the media discourse of Hezbollah - El Zein, Hatem (Universiti Kebangsaan Malaysian, 2014)
This paper aims to identify media discourse of “The Islamic Resistance”, the military arm of Lebanese Hezbollah. On contrary to many researches, this paper is significant, because it distinguishes between media discourse of “The Islamic Resistance” and media discourse of Hezbollah. With the existence of many military media units linked directly to military wings of organisations in the Middle East, this paper provides an example on how to identify media discourse of a military arm.